ICA SAHR – A Legacy of the DDR: The Stasi Records Archive - Dagmar Hovestädt - ICA International Council on Archives (2023)
Dagmar Hovestädt, head of outreach and research at the Stasi Records Archive at the Federal Archives in Germany presents A Legacy of the DDR: The Stasi Records Archive. Dagmar Hovestädt was the spokeswoman of the Federal Commissioner for the Stasi Records (BStU) from 2011 to 2021. Currently she heads the department outreach and research at the Stasi Records Archive at the Federal Archives in Germany. As part of her duties, she implements strategy on continued research into the Stasi records as well as on public education, exhibitions, events and the development of the historic site of the Ministry for State Security into a "Campus for Democracy". She is part of an initiative to form an international human rights archive network and is speaking and writing on the role of archives in transitional justice. She received a master’s degree in communication and political science from the Berlin Free University in 1991, after which she worked as a journalist in Berlin from 1989 to 1999 and for German media from the USA from 2000 to 2011. As a direct result of the Peaceful Revolution of 1989 the records of the Ministry for State Security, the secret police in the service of the East German communist party SED, were made available to the public, to address the injustices of the communist past in the united Germany. Unlike many other Eastern European countries, the unique post-conflict situation of the unification of the two Germanys allowed for immediate access to these records in support of many transitional justice mechanisms in dealing with the past. This talk will present the special conditions of the German process, the effects upon the role of the archive, and its future potential. After 30 years of active participation in shaping the dialogue about the past, the Stasi Records Archive now part of the Federal Archives (Bundesarchiv) seems poised for a continuing role in the safeguarding of democracy and human rights for the coming generations.